Carbonatation and Decarbonatation Kinetics in the La2O3-La2O2CO3 System under CO2 Gas Flows. (23rd August 2010) - Bakiz, Bahcine; Guinneton, Frédéric; Arab, Madjid; Benlhachemi, Abdeljalil; Villain, Sylvie; Satre, Pierre; Gavarri, Jean-Raymond
Abstract : The carbonatation of La2 O3 oxide and the decarbonatation of lanthanum carbonate phase La2 O2 CO3 are investigated using thermal and thermogravimetry analyses under CO2 gas flow. The initial phase La2 O3 is first elaborated from pyrolysis of a LaOHCO3 precursor. Then, thermal and thermogravimetry analyses are carried out under CO2 flow, as temperature increases then decreases. The carbonatation kinetics of La2 O3 is determined at three fixed temperatures. Electrical impedance spectroscopy is performed to determine the electrical responses associated with ionic mobilities and phase changes, in the temperature range 25 to900 ∘ C. The electrical conduction during heating underCO 2 gas flow should be linked to two regimes of ionic conduction of the carbonate ions. From these electrical measurements, the ionic mobility of carbonate ionsCO 3     2 − is found to be close to 0.003 ·10 − 4  cm 2  s − 1  V − 1 at750 ∘ C for the monoclinic La2 O2 CO3 phase.